Pelatihan Merancang Perangkat Pembelajaran Kurikulum 2013 Bagi Guru SMA Swasta (SMAS) LKMD Kandis Kabupaten Siak - Indriyanto Indriyanto; Afriza Rahma Rani (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
Community service activities regarding designing 2013 curriculum learning tools for LKMD Kandis private high school (Smas) teachers, in line with the Ministry of Education and Culture's program, that the 2013 curriculum must be realized starting in June 2014 in all schools, including schools in the Kandis area of Siak district. The training on designing learning tools was attended by 20 participants, this was due to other teachers being busy in routine activities. The end product is the existence of learning tools, and enlightenment about the implementation of the 2013 curriculum. Even though the room conditions have limitations (using classrooms without air conditioning), the enthusiasm of the participants remains high.